Hazon Gabriel: New Readings of the Gabriel Revelation - Henze, Matthias (Society of Biblical Literature, 2014)
Intro -- Contents -- Abbreviations -- Preface -- The Jeselsohn Stone: Discovery and Publication -- A Hebrew Prophetic Text on Stone from the Early Herodian Period: A Preliminary Report -- Notes on the So-Called Gabriel Vision Inscription -- The Apocalyptic and Messianic Dimensions of the Gabriel Revelation in Their Historical Context -- Hazon Gabriel: A Grammatical Sketch -- Response to Israel Knohl, Messiahs and Resurrection in "The Gabriel Revelation -- Gabriel and David: Some Reflections on an Enigmatic Text -- Some Observations on the Hazon Gabriel -- Hosts, Holy Ones, and Words of Gabriel: The Angelology of Hazon Gabriel in the Context of Second Temple and Late Antique Literature -- The Use of Daniel in the Gabriel Revelation -- "Jerusalem" in the Gabriel Revelation and the Revelation of John -- Bibliography -- Contributors -- Index of Passages -- Index of Names and Subjects -- Index of Authors.